ISLAM SEBAGAI SUMBER HUKUM NASIONAL DI INDONESIA - Nadila; Surya Sukti; Mustar (PT. Hasba Edukasi Mandiri, 2026)
The position of Islamic law within Indonesia’s national legal system reflects an unresolved tension between the religious aspirations of society and the construction of a modern rule-of-law state. This study aims to critically examine the position and integration patterns of Islamic law within the national legal framework. Employing a normative legal research method with statutory and conceptual approaches, this study relies on recent scholarly literature. The findings reveal that Islamic law is predominantly positioned as a source of material law rather than as a formal legal system, resulting in a partial and selective integration process heavily influenced by legal-political configurations. Its dominance in family law and Islamic finance indicates a structural limitation that confines Islamic law to the private sphere. This condition suggests that integration remains largely symbolic and instrumental rather than substantive. Furthermore, the existing model of legal pluralism demonstrates a semi-integrative character under state control, thereby limiting the autonomous development of Islamic law. Key challenges include epistemological diversity, political contestation, and the need to align with universal principles such as human rights and democracy. Therefore, a more critical and progressive approach is required to ensure that the integration of Islamic law moves beyond formal recognition toward achieving substantive justice within the national legal system.